An Analysis of the Influence of Deviant Car Drivers in North Maluku - Armanto Umanailo; Sabarudin; Nurmaiyasa Marsaoly (East Asian Journal of Multidisciplinary Research, 2022)
The deviant behavior of car drivers becomes a concern for the North Halmahera Police in handling the risk of accidents along the Sofifi-Tobelo road. Theerefore, this study focuses on identifying the effect of gender on the deviant behavior of car drivers, identifying the effect of age on the deviant behavior of car drivers, identifying the effect of education level on the deviant behavior of car drivers, identifying type of work on the deviant behavior of car drivers, and identifying the effect of gender, age, education level, and type of work simultaneously on the deviant behavior of car drivers on the Sofifi Tobelo road, North Halmahera Regency, North Maluku Province. The quantitative descriptive research was used as a tool to obtain significant findings from a number of research variables involved. The results of this research is expected to  be an in-depth evaluation for the increasing incidence of traffic accidents along the Sofifi-Tobelo road, particularly, in five accident-prone points, namely Mount Cut, Dum Village, Paca Village, Tanjung Barnabas and Bori Village.